INTERVENSI PEMASARAN SOSIAL UNTUK MENINGKATKAN NIAT BERWIRAUSAHA HIJAU DI KALANGAN MAHASISWA DI BALI - Santika, I Wayan; Agus Satria Pramudana, Komang; Pharamadita, I Putu Agus Wenta; Tamaja, Ketut Wahyu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024DO - 10.24843/EEB.2024.v13.i01.p01, 2024)
This research is motivated by the low intention of green entrepreneurship among university students in Bali. The purpose of this study was to analyze social marketing interventions through entrepreneurship education and institutional infrastructure support in increasing green entrepreneurial intentions among university students in Bali. The data in this study were obtained by distributing questionnaires to students in Bali. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. The results of the study show that entrepreneurship education has a positive and significant effect on green entrepreneurial intention. Entrepreneurship education has a positive and significant effect on attitude toward behavior, subjective norms, and perceived behavioral control. Attitude toward behavior, subjective norms, and perceived behavioral control have a positive and significant effect on green entrepreneurial intention. Institutional infrastructure support positively and significantly moderates the effect of attitude toward behavior, subjective norms, perceived behavioral control on green entrepreneurial intention. The theoretical implication of this research is to strengthen the Theory of Planned Behavior and Social Marketing as a reliable theory to explain and predict the formation of green entrepreneurial behavior among university students.